Epidemiological landscape of tongue cancer in younger patients in a National Cancer Center in Brazil - Ana Carolina da Silva Souto; Beatriz Nascimento Monteiro da Silva; Fernanda Vieira Heimlich; Otávio Augusto Brioschi Soares; Fernando Luiz Dias; Luiz Henrique de Lima Araujo; Andreia Cristina de Melo; Héliton Spindola Antunes; Luiz Claudio Santos Thuler; Daniel Cohen Goldemberg (Scientific Reports)
Abstract This study investigates the changing epidemiological profile of tongue squamous cell carcinoma (SCC) to young patients, highlighting its rising incidence among non-traditional risk groups. A retrospective descriptive study was conducted, covering data from medical records between 2000 and 2012. Patients were categorised into two age groups (≤ 40 years; 41–50 years). Sociodemographic and clinicopathological characteristics were evaluated. A total of 108 patients participated, mostly aged 41–50. Alcohol consumption (43.3%) surpassed smoking. Majority (56.7%) aged ≤ 40 never smoked. Lateral tongue border was most affected, with stages III and IV prevalent. Patients aged ≤ 40 were mostly eligible for surgery (44%). Survival tied to staging and surgery; age had no significant impact. Young squamous cell carcinoma patients often lacked traditional risk factors like smoking, underwent surgery, and typically had disease-free margins. The study underscores the importance of broad external policies for early diagnosis, beyond just traditional risk groups.